Is hypoxia training good for muscles and exercise performance? - Vogt, M.; Hoppeler, H. (Progress in Cardiovascular Diseases, 2010)
Altitude training has become very popular among athletes as a means to further increase exercise performance at sea level or to acclimatize to competition at altitude. Several approaches have evolved during the last few decades, with "live high-train low" and "live low-train high" being the most popular. This review focuses on functional, muscular, and practical aspects derived from extensive research on the "live low-train high" approach. According to this, subjects train in hypoxia but remain under normoxia for the rest of the time. It has been reasoned that exercising in hypoxia could increase the training stimulus. Hypoxia training studies published in the past have varied considerably in altitude (2300-5700 m) and training duration (10 days to 8 weeks) and the fitness of the subjects. The evidence from muscle structural, biochemical, and molecular findings point to a specific role of hypoxia in endurance training. However, based on the available performance capacity data such as maximal oxygen uptake (Vo2max) and (maximal) power output, hypoxia as a supplement to training is not consistently found to be advantageous for performance at sea level. Stronger evidence exists for benefits of hypoxic training on performance at altitude. "Live low-train high" may thus be considered when altitude acclimatization is not an option. In addition, the complex pattern of gene expression adaptations induced by supplemental training in hypoxia, but not normoxia, suggest that muscle tissue specifically responds to hypoxia. Whether and to what degree these gene expression changes translate into significant changes in protein concentrations that are ultimately responsible for observable structural or functional phenotypes remains open. It is conceivable that the global functional markers such as Vo2max and (maximal) power output are too coarse to detect more subtle changes that might still be functionally relevant, at least to high-level athletes.